Metabolic engineering provides insight into the regulation of thiamin biosynthesis in plants. Issue 4 (4th May 2021) - Strobbe, Simon; Verstraete, Jana; Stove, Christophe; Van Der Straeten, Dominique
Abstract : Metabolic engineering of thiamin (vitamin B1) content emphasizes the need to balance the two branches of B1 biosynthesis and uncovers the importance of B1 salvage to improve engineering strategies. Abstract: Thiamin (or thiamine) is a water-soluble B-vitamin (B1), which is required, in the form of thiamin pyrophosphate, as an essential cofactor in crucial carbon metabolism reactions in all forms of life. To ensure adequate metabolic functioning, humans rely on a sufficient dietary supply of thiamin. Increasing thiamin levels in plants via metabolic engineering is a powerful strategy to alleviate vitamin B1 malnutrition and thus improve global human health. These engineering strategies rely on comprehensive knowledge of plant thiamin metabolism and its regulation. Here, multiple metabolic engineering strategies were examined in the model plant Arabidopsis thaliana . This was achieved by constitutive overexpression of the three biosynthesis genes responsible for B1 synthesis, HMP-P synthase (THIC ), HET-P synthase ( THI1 ), and HMP-P kinase/TMP pyrophosphorylase ( TH1 ), either separate or in combination. By monitoring the levels of thiamin, its phosphorylated entities, and its biosynthetic intermediates, we gained insight into the effect of either strategy on thiamin biosynthesis. Moreover, expression analysis of thiamin biosynthesis genes showed the plant's intriguing ability to respond to alterations in the pathway. Overall, we revealed the necessity to balance the pyrimidine and thiazole branches of thiamin biosynthesis and assessed its biosynthetic intermediates. Furthermore, the accumulation of nonphosphorylated intermediates demonstrated the inefficiency of endogenous thiamin salvage mechanisms. These results serve as guidelines in the development of novel thiamin metabolic engineering strategies.